MODEL FOR ENGLISH CONVERSATION ON GUIDING SERVICES - Tegar, M.Tegar Pratama; Herlina; Evi Rosmiyati (SMART: Journal of Multidisciplinary Educational, 2024)
This study aims to produce a Model for English Conversation pocket book for guidance services that can help add to student teaching materials. The researcher used the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) method but only reached the implementation stage due to time and cost constraints. The research was conducted at SMK Negeri 6 Palembang, where the researcher tried to test the feasibility of the pocket books made by students. data collection techniques using questionnaires and documentation. Based on the results of this study, it was obtained 86.6% from material experts and 83.7% from media experts, so this pocket book is included in the ''valid'' category with revision. The student response questionnaire scored 89.7%, so this pocket book was declared practical. Thus, the Pocket Book Model for English Conversation on Guiding Services is very appropriate to be used to add to student teaching materials.